Impact of cumulative cisplatin dose in childhood nasopharyngeal carcinoma based on neoadjuvant chemotherapy response in the intensity-modulated radiotherapy era: a real-world study - Ya-Nan Jin (BMC, 2021)
Abstract Background We aimed to comprehensively investigate the optimal cumulative cisplatin dose during concurrent chemoradiotherapy (CC-CCD) for locoregionally advanced nasopharyngeal carcinoma (CA-LANPC) with different tumor responses after neoadjuvant chemotherapy (NAC). Methods Patients with CA-LANPC who underwent NAC followed by cisplatin-based concurrent chemoradiotherapy were retrospectively analyzed. Evaluation of tumor response in patients was conducted by Response Evaluation Criteria for Solid Tumor (RECIST) 1.1 after two to four cycles NAC. Multivariate Cox proportional hazards models were used for prognosis. Recursive partitioning analysis (RPA) was conducted to classify participates and predict disease-free survival (DFS). Results One hundred and thirty-two patients with favorable response after NAC were included. The median CC-CCD was 163 mg/m2 (IQR, 145–194 mg/m2), and 160 mg/m2 was selected as the cutoff point to group patients into low and high CC-CCD groups (< 160 vs. ≥ 160 mg/m2). There was significant improvement in 5-year DFS (91.2% vs. 72.6%; P = 0.003) for patients receiving high CC-CCD compared to those receiving low CC-CCD. Multivariate analysis revealed that CC-CCD, T stage, and Epstein–Barr virus (EBV) DNA were independent prognostic factors for DFS (P < 0.05 for all). Patients were further categorized into two prognostic groups by RPA: the low-risk group (T1-3 disease with regardless of EBV DNA, and T4 disease with EBV DNA < 4000 copy/mL), and the high-risk group (T4 disease with EBV DNA ≥ 4000 copy/mL). Significant 5-year DFS improvement was observed for the high-risk group (P = 0.004) with high CC-CCD. However, DFS improvement was relatively insignificant in the low-risk group (P = 0.073). Conclusions CC-CCD was a positive prognostic factor for responders after NAC in CA-LANPC. Furthermore, CC-CCD ≥ 160 mg/m2 could significantly improve DFS in the high-risk group with CA-LANPC, but the benefit of high CC-CCD in the low-risk group needs further study.